Australian healthcare professionals' perspectives and experiences on screening and monitoring islet autoimmunity: A qualitative exploration - Mia Majstorovic; Kelly J. McGorm; John M. Wentworth; Alyssa Sawyer; Melissa Oxlad; Jennifer J. Couper (Diabetic Medicine, 2026)
Abstract Aims Islet autoantibodies characterise a period of immune‐mediated destruction preceding clinical (symptomatic) type 1 diabetes. Screening and monitoring programmes for islet autoimmunity are being planned and implemented globally. The perspectives and experiences of healthcare professionals working in paediatric screening and monitoring of islet autoimmunity and clinical type 1 diabetes can inform these programmes. Methods We interviewed 32 healthcare professionals (81% women) caring for children with islet autoimmunity and/or clinical type 1 diabetes in Australia (median of 13 years of type 1 diabetes clinical experience). Data were analysed using reflexive thematic analysis. Results We developed seven themes: 1. implementing population screening and monitoring is contested, 2. considerations for the structure of screening and monitoring, 3. prioritising equitable access and convenience, 4. focus on managing children's testing experiences, 5. potential psychological impacts of islet autoimmunity on children, 6. caregivers' perceived coping ability and associated responses to screening and monitoring and 7. importance of relationships with and support from healthcare professionals. Participants expressed benefits, concerns and considerations necessary for the well‐organised, equitable and acceptable implementation of screening and monitoring. They described varying effects of testing and islet autoimmunity on families, emphasising the importance of trusted relationships between families and healthcare professionals. Conclusions Healthcare professionals' insights can guide how screening and monitoring programmes are designed and implemented, particularly in justifying their introduction, ensuring equitable care and reducing adverse impacts on families. Further research will focus on the experiences of children and caregivers to integrate wider input into the design of these programmes.